NATO's Eastern Agenda in a New Strategic Era - Larrabee, F. Stephen (RAND Corporation, 2023)
NATO's Eastern agenda faces several challenges, including consolidating the democratic transitions in Central and Eastern Europe, ensuring the security of the Baltic states, developing a post-NATO-enlargement strategy for Ukraine, deepening the Russia-NATO partnership, and engaging the Caucasus and Central Asia. The author also considers NATO's broader transformation.